Draft Annual Plan 1995-96 Volume - I Government of Karnataka - Planning Commission (Planning Commission, 1995)
Although Eighth Five Year Plan (1992-97) commenced from 1992-93, the annual plan 1992-93 was formulated much before the finalisation of Eight Five Year Plan which was finalised only by May 1992. The Eighth Plan envisages, among other things, a significant step up in plan investment in the State, more than doubling of plan investment in real terms compared to the expenditure during the Seventh Five Year Plan. The approved outlay of the States Eighth Five Year Plan is Rs.12300 crores at 1991-92 prices.
Government of Karnataka